Testing device for researching crystallization characteristics of electrolyte of iron-chromium flow battery
By designing a test device for iron-chromium flow batteries, including crystallizers, stirrers and online detectors, the problem of difficult to observe the crystallization of electrolytes at low temperatures is solved, and the crystallization characteristics test of electrolytes in different states of charge is achieved , ensuring the accuracy of the test and the stability of the electrolyte.
Patent Information
- Application Number
- CN202420711294.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Utility models(China)
- Current Assignee / Owner
- Filing Date
- 2024-04-08
- Publication Date
- 2024-12-27
- Estimated Expiration
- 2034-04-08
AI Technical Summary
The iron-chromium flow battery electrolyte is prone to crystallization at low temperatures, and because it is difficult to observe crystallization changes in acidic mixed salt environments, the prior art lacks effective crystallization characteristic data.
A test device including a crystallizer, a refrigerator, agitator and an online crystal detector was designed. The crystal grain generation and size in the electrolyte are detected in real time through the detector probe. The stirring function keeps the sample uniform, and the electrolyte is protected by an inert gas. Prevent oxidation and realize the crystallization characteristics test of electrolytes of different charged states.
The crystallization temperature test of the dark-colored and easy-to-oxidize solution can be tested online in real time, accurately measured the crystallization temperature, and prevent the electrolyte from deteriorating. It is suitable for studying the application temperature range of iron-chromium flow batteries, and avoiding the setting of temperature ranges. Improper electrolyte crystallization problems.
Smart Images

Figure CN222259217U_ABST
Abstract
Description
Technical Field
[0001] The utility model belongs to the technical field of liquid flow batteries, and particularly relates to a testing device for studying crystallization characteristics of electrolyte of an iron-chromium liquid flow battery. Background Art
[0002] The electrolyte of the iron-chromium flow battery is easy to crystallize at low temperatures, especially when it contains chromium dichloride, an intermediate product in the charging and discharging process. Since chromium dichloride is easily oxidized in humid air and its environment is an acidic mixed salt solution, there is currently no data on its crystallization characteristics in a mixed acidic salt environment. The electrolyte used in the iron-chromium flow battery contains a large amount of ferrous ions and trivalent chromium ions, and the color is a relatively dark green, and it is difficult to observe the crystallization changes with the naked eye. Therefore, it is necessary to design a new test device for the crystallization characteristics of the iron-chromium flow battery electrolyte. Utility Model Content
[0003] In view of the above problems, the utility model discloses a testing device for studying the crystallization characteristics of an electrolyte of an iron-chromium flow battery, comprising: a crystallizer, a refrigerator, a stirrer and an online crystallization detector;
[0004] The online crystallization detector is connected to a detector probe;
[0005] The detector probe extends 2 to 3 cm below the liquid surface of the crystallizer;
[0006] The agitator is connected to the crystallizer;
[0007] The refrigerator is connected to the crystallizer through a pipeline.
[0008] Furthermore, the stirrer includes a motor, a stirring shaft and a stirring blade;
[0009] The motor is connected to one end of the stirring shaft;
[0010] The other end of the stirring shaft is connected to the stirring blade;
[0011] The stirring blade extends below the liquid level of the crystallizer;
[0012] The rotation speed of the stirrer is set to 60-480 r / min.
[0013] Furthermore, it also includes: a bracket;
[0014] The bracket is fixedly connected to the online crystallization detector and is used for fixing the online crystallization detector.
[0015] Furthermore, it also includes: a high-purity air bottle;
[0016] The high-purity air bottle is connected to the online crystallization detector through a pipeline.
[0017] Furthermore, it also includes: a first pressure reducing valve;
[0018] The outlet of the high-purity air bottle is provided with a first pressure reducing valve;
[0019] One end of the first pressure reducing valve is connected to the online crystallization detector through a pipeline;
[0020] The first pressure reducing valve is set to 0.2-0.4 MPa.
[0021] Furthermore, it also includes: a high purity nitrogen cylinder;
[0022] The high-purity nitrogen bottle is connected to the crystallizer through a pipeline.
[0023] Furthermore, it also includes: a second pressure reducing valve;
[0024] The outlet of the high-purity nitrogen cylinder is provided with a second pressure reducing valve;
[0025] One end of the second pressure reducing valve is connected to the crystallizer through a pipeline;
[0026] The second pressure reducing valve is set to 0.3-0.5 MPa.
[0027] Furthermore, it also includes: a control unit;
[0028] The control unit is electrically connected to the refrigerator, the stirrer and the online crystallization detector respectively.
[0029] Furthermore, the crystallizer is provided with four interfaces.
[0030] Compared with the prior art, the beneficial effects of the utility model are:
[0031] 1. The test device of the utility model can protect the ion state in the electrolyte through inert gas in real time to isolate air or other substances, prevent the change of its redox state (that is, prevent the SOC state of the electrolyte from changing during the test process), and ensure that the sample to be tested does not deteriorate;
[0032] 2. The electrolyte used in redox flow batteries is usually dark in color. The crystals produced by the solution crystallization are difficult to observe with the naked eye, and the growth process of fine crystals cannot be observed. The use of an online crystallization detector can display the generation and size of crystals in the solution in real time online, and can measure the crystallization temperature more accurately.
[0033] 3. The stirring function keeps the sample in a uniform state at all times;
[0034] 4. The test device of the utility model can be used to test and analyze the crystallization characteristics of electrolytes for iron-chromium flow batteries with different SOCs. The test process is visualized and the crystallization phenomenon is analyzed online in real time. It can be well applied to the crystallization temperature test of dark-colored and easily oxidizable solution samples.
[0035] Other features and advantages of the utility model will be described in the following description, and partly become apparent from the description, or understood by implementing the utility model. The purpose and other advantages of the utility model can be realized and obtained by the structures indicated in the description and the drawings. BRIEF DESCRIPTION OF THE DRAWINGS
[0036] In order to more clearly illustrate the embodiments of the utility model or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some embodiments of the utility model. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0037] Figure 1 A schematic structural diagram of a testing device for studying the crystallization characteristics of an electrolyte of an iron-chromium flow battery according to an embodiment of the utility model is shown.
[0038] Figure numerals: 1. bracket; 2. detector probe; 3. crystallizer; 4. refrigerator; 5. agitator; 6. online crystallization detector; 7. high-purity air bottle; 8. high-purity nitrogen bottle; 9. first pressure reducing valve; 10. second pressure reducing valve. DETAILED DESCRIPTION
[0039] In order to make the purpose, technical solution and advantages of the embodiment of the utility model clearer, the technical solution in the embodiment of the utility model will be clearly and completely described below in conjunction with the drawings in the embodiment of the utility model. Obviously, the described embodiment is a part of the embodiment of the utility model, not all of the embodiments. Based on the embodiment of the utility model, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the utility model.
[0040] Figure 1 The schematic diagram of the structure of the testing device for studying the crystallization characteristics of the electrolyte of the iron-chromium flow battery according to the embodiment of the utility model is shown. Figure 1 As shown, the utility model proposes a test device for studying the crystallization characteristics of the electrolyte of the iron-chromium flow battery, comprising: a crystallizer 3, a refrigerator 4, a stirrer 5 and an online crystallization detector 6;
[0041] The online crystallization detector 6 is connected to a detector probe 2;
[0042] The lower end of the detector probe 2 extends 2 to 3 cm below the liquid surface of the crystallizer 3 to ensure that it does not contact the crystallizer wall and the agitator 5, so as to achieve the best detection effect;
[0043] The stirrer 5 is connected to the crystallizer 3;
[0044] The refrigerator 4 is connected to the crystallizer 3 through a pipeline.
[0045] The detector probe 2 is used to extend into the electrolyte and display the electrolyte state in real time;
[0046] Crystallizer 3, the inner layer is filled with electrolyte, and the outer layer is passed through the flowing cooling medium to create a low temperature environment;
[0047] A refrigerator 4, used to control the temperature of the electrolyte in the crystallizer 3;
[0048] Agitator 5, used to make the electrolyte in the crystallizer 3 uniform and display the liquid temperature;
[0049] The online crystallization detector 6 is used for online detection of whether crystal grains are generated in the electrolyte.
[0050] The electrolyte used in redox flow batteries usually has a darker color. The crystals produced by the crystallization of the solution are difficult to observe with the naked eye, and the growth process of the fine crystals cannot be observed. The use of an online crystallization detector 6 can display the generation and size of the crystals in the solution in real time online, and can measure the crystallization temperature more accurately.
[0051] The test device for studying the crystallization characteristics of the iron-chromium liquid flow battery electrolyte of the utility model can accurately measure the crystallization characteristics of electrolytes in different charge states, which is helpful for studying the application temperature range of the liquid flow battery, and then serves the engineering design, avoiding a series of problems caused by electrolyte crystallization due to improper temperature range setting.
[0052] In some embodiments, the stirrer 5 includes a housing, a motor, a stirring shaft and a stirring blade;
[0053] A motor is arranged in the housing, and a display screen is also arranged on the housing to display the temperature of the electrolyte;
[0054] The motor is connected to one end of the stirring shaft;
[0055] The other end of the stirring shaft is fixedly connected to the stirring blade;
[0056] The stirring blade extends below the liquid level of the crystallizer 3;
[0057] The rotation speed of the stirrer 5 is set to 60-480 r / min. Preferably, the rotation speed of the stirrer 5 is set to 120-240 r / min to keep the electrolyte in a uniform state.
[0058] In some embodiments, a temperature measuring probe is also provided at the end of the stirring shaft for measuring the temperature of the electrolyte.
[0059] The stirring blades of the stirrer 5 stir the electrolyte to keep the electrolyte uniform, and the measured electrolyte temperature is displayed on the display screen.
[0060] In some embodiments, the testing device for studying the crystallization characteristics of the electrolyte of the iron-chromium flow battery further includes: a bracket 1;
[0061] The bracket 1 is fixedly connected to the online crystallization detector 6 and is used to fix the online crystallization detector 6 .
[0062] In some embodiments, the testing device for studying the crystallization characteristics of the electrolyte of the iron-chromium flow battery further includes: a high-purity air bottle 7;
[0063] The high-purity air bottle 7 is connected to the online crystallization detector 6 through a pipeline.
[0064] The high-purity air bottle 7 supplies high-purity air to the online crystallization detector 6 to cool the online crystallization detector 6 so that the online crystallization detector 6 works within a rated temperature range.
[0065] In some embodiments, the testing device for studying the crystallization characteristics of the electrolyte of the iron-chromium flow battery further includes: a first pressure reducing valve 9;
[0066] The outlet of the high-purity air bottle 7 is provided with a first pressure reducing valve 9;
[0067] One end of the first pressure reducing valve 9 is connected to the online crystallization detector 6 through a pipeline;
[0068] The first pressure reducing valve 9 is set to 0.2-0.4 MPa.
[0069] The first pressure reducing valve 9 is used to control the air flow rate by setting the valve pressure.
[0070] In some embodiments, the testing device for studying the crystallization characteristics of the electrolyte of the iron-chromium flow battery further includes: a high-purity nitrogen gas bottle 8;
[0071] The high-purity nitrogen bottle 8 is connected to the crystallizer 3 through a pipeline.
[0072] The high-purity nitrogen bottle 8 is used to supply high-purity nitrogen to the crystallizer 3. The high-purity nitrogen can effectively prevent the electrolyte from being oxidized.
[0073] In some embodiments, the testing device for studying the crystallization characteristics of the electrolyte of the iron-chromium flow battery further includes: a second pressure reducing valve 10;
[0074] The outlet of the high-purity nitrogen bottle 8 is provided with a second pressure reducing valve 10;
[0075] One end of the second pressure reducing valve 10 is connected to the crystallizer 3 through a pipeline;
[0076] The second pressure reducing valve 10 is set to 0.3-0.5 MPa.
[0077] The second pressure reducing valve 10 is used to control the flow rate of the inert gas by setting the valve pressure.
[0078] The test device for studying the crystallization characteristics of the electrolyte of the iron-chromium liquid flow battery of the utility model can protect the ion state in the electrolyte by isolating the air or other substances through the inert gas in real time, thereby preventing the change of its redox state (that is, preventing the SOC state of the electrolyte from being changed during the test), thereby ensuring that the sample to be tested does not deteriorate.
[0079] In some embodiments, the testing device for studying the crystallization characteristics of an electrolyte of an iron-chromium flow battery further includes: a control unit;
[0080] The control unit is electrically connected to the refrigerator 4, the stirrer 5 and the online crystallization detector 6 respectively, collects the temperature data of the electrolyte, the detection result of whether the electrolyte has crystallization, and controls the working status of the refrigerator 4, the stirrer 5 and the online crystallization detector 6 according to the settings.
[0081] In some embodiments, the crystallizer 3 is provided with four interfaces, wherein the first interface is connected to the high-purity nitrogen bottle 8 through a pipeline, the second interface is used to access the detector probe 2, the third interface is used to access the agitator 5, and the fourth interface is used to discharge the tail gas.
[0082] Since the electrolyte used in the iron-chromium flow battery does not contain chromium dichloride, the electrolyte is charged using an electrochemical workstation so that the electrolyte has a certain charge state. At this time, part of the chromium trichloride undergoes an electrochemical reaction and is converted into chromium dichloride:
[0083] Negative electrode reaction:
[0084] Depending on the degree of charge, different concentration ratios of CrCl can be obtained. 3 and CrCl 2 Solution, in the field of iron-chromium flow batteries, is manifested as electrolytes of different states of charge (SOC). In energy storage applications, it is very important to explore the crystallization characteristics of electrolytes of different SOCs, which can help study the application temperature range of the flow battery, and then serve the engineering design, avoiding a series of problems caused by electrolyte crystallization due to improper temperature range setting.
[0085] The crystallization characteristics of the electrolyte of the iron-chromium flow battery with different SOCs were tested. The above test device for studying the crystallization characteristics of the electrolyte of the iron-chromium flow battery was built. The specific test method and process are as follows:
[0086] Example 1
[0087] Step 1: Select analytically pure ferrous chloride and chromic chloride raw materials and high-purity hydrochloric acid to prepare a mixed solution, the concentrations of the three drugs are 0.1M to 5M, and a certain amount of M ions are added, the M ions include one or more of sodium ions, potassium ions, calcium ions, ammonium ions, oxalic acid, and ethylene glycol, the concentration range is 0.001M to 0.5M or 0.1wt% to 2wt%, and the remaining substance is pure water.
[0088] The single battery test system disclosed in the Chinese patent (publication number CN212750938U) uses a charger and a discharger to charge the electrolyte with a SOC of 0%, and constant current charging can be selected, and the charging current is 1A to 14A;
[0089] Step 2: Step 1 can obtain electrolytes with different SOCs, which are 5%, 10%, 15%, 20%, 30%, 40%, 50%, 60%, 70%, 75%, 80%, and 85% SOC negative electrode electrolytes, numbered 1-12 from left to right;
[0090] Step 3: The electrolytes obtained in step 2 are sealed and stored in an airtight manner;
[0091] Step 4: Open the first pressure reducing valve 9 and the second pressure reducing valve 10 of the crystallization test device, continuously purge the crystallizer 3 with inert gas at a flow rate of 300 ml / min for 10 min, continuously purge the online crystallization detector 6 with high-purity air, and turn on the refrigerator 4 to set it to -10°C;
[0092] Step 5: Take 350 ml of electrolyte No. 1 and place it in the crystallizer 3, turn on the agitator 5 and the circulation pump of the refrigerator 4, and continue to cool the electrolyte sample while monitoring the temperature of the liquid to be tested;
[0093] Step 6: When the temperature of the liquid in the crystallizer 3 is -10°C, observe whether small crystals are generated in the liquid on a notebook connected to the online crystallization detector 6, and keep recording for 10 to 30 minutes;
[0094] Step 7: If it is observed in step 6 that crystals are generated and grow in the electrolyte, then at -10°C, electrolyte No. 1 can already crystallize. To obtain the crystallization temperature of electrolyte No. 1, the refrigerator setting temperature is increased to -5°C. When the liquid temperature in the crystallizer 3 is -5°C, observe whether small crystals are generated in the liquid on a notebook connected to the online crystallization detector 6, and keep recording for 10 to 30 minutes;
[0095] Step 8: If it is observed in step 7 that no crystals are generated in the electrolyte, then at -5°C, electrolyte No. 1 does not reach the crystallization condition. To obtain the crystallization temperature of electrolyte No. 1, the temperature of refrigerator 4 is lowered to -7.5°C. When the liquid temperature in crystallizer 3 is -7.5°C, observe whether small crystals are generated in the liquid on a notebook connected to the online crystallization detector 6, and keep recording for 10 to 30 minutes;
[0096] Step 9: Observe whether the electrolyte in step 8 produces grains. If not, its crystallization temperature is considered to be -8.75°C. If grains are produced, its crystallization temperature is considered to be -6.25°C.
[0097] Step 10: The test steps can be simplified according to the test accuracy requirements.
[0098] Step 11: Determine the crystallization temperature of the remaining electrolytes No. 2-12 according to the above method.
[0099] Example 2
[0100] Step 1: Select analytically pure ferrous chloride and chromic chloride raw materials and high-purity hydrochloric acid to prepare a mixed solution, in which the concentration of ferrous chloride is 1M, the concentration of chromic chloride is 1M, the concentration of hydrochloric acid is 3M, and 1mM of ammonium chloride, calcium chloride, sodium chloride and 0.5wt% of ethylene glycol are added. The SOC of the newly prepared electrolyte is 0%.
[0101] 800 ml of the obtained electrolyte was taken and respectively loaded into the positive and negative electrode storage tanks (400 ml each), and the electrolyte with a SOC of 0% was charged with a constant current of 7 A using a charging and discharging machine on a single battery test system disclosed in a Chinese patent (publication number CN212750938U);
[0102] Step 2: Step 1 can obtain electrolytes with different SOCs, which are 5%, 10%, 15%, 20%, 30%, 40%, 50%, 60%, 70%, 75%, 80%, and 85% SOC negative electrode electrolytes, which are numbered 1-12 from left to right, as shown in Table 1;
[0103] Table 1 Relationship between different SOC electrolytes and charging time
[0104] Electrolyte No. SOC Charging time / s 1 5% 275.67 2 10% 551.34 3 15% 827.01 4 20% 1102.69 5 30% 1654.03 6 40% 2205.37 7 50% 2756.71 8 60% 3308.06 9 70% 3859.40 10 75% 4135.07 11 80% 4410.74 12 85% 4686.41
[0105] Step 3: The electrolytes obtained in step 2 are sealed and stored in an airtight manner, and 350 ml of electrolyte No. 2 is taken for crystallinity test;
[0106] Step 4: Open the first pressure reducing valve 9 and the second pressure reducing valve 10 of the crystallization test device, continuously purge the crystallizer 3 with high-purity nitrogen, continuously purge the online crystallization detector 6 with high-purity air, and turn on the refrigerator 4 and set it to -10°C;
[0107] Step 5: Take 350 ml of electrolyte No. 2 and place it in the crystallizer 3, turn on the agitator 5, and continue to cool the electrolyte while monitoring the liquid temperature;
[0108] Step 6: When the liquid temperature in the crystallizer 3 is -10°C, observe whether small crystals are generated in the liquid on a notebook connected to the online crystallization detector 6, and keep recording for 20 minutes;
[0109] Step 7: If no small crystals are observed in step 6, the temperature of the refrigerator 4 is further lowered to -15°C. When the liquid temperature in the crystallizer 3 is -15°C, observe whether small crystals are generated in the liquid on a notebook connected to the online crystallization detector 6, and continue recording for 20 minutes;
[0110] Step 8: If no small crystals are observed in step 7, the temperature of the refrigerator 4 is further lowered to -20°C. When the liquid temperature in the crystallizer 3 is -20°C, observe whether small crystals are generated in the liquid on a notebook connected to the online crystallization detector 6, and continue recording for 20 minutes;
[0111] Step 9: If no small crystals are observed in step 8, the temperature of the refrigerator 4 is further lowered to -25°C. When the liquid temperature in the crystallizer 3 is -25°C, observe whether small crystals are generated in the liquid on a notebook connected to the online crystallization detector 6, and continue recording for 20 minutes;
[0112] Step 10: If no small crystal grains are observed in step 9, the temperature of the refrigerator 4 is further lowered to -30°C. When the liquid temperature in the crystallizer 3 is -30°C, observe whether small crystal grains are generated in the liquid on a notebook connected to the online crystallization detector 6, and continue recording for 20 minutes;
[0113] Step 11: If no small crystal grains are observed in step 10, the temperature of the refrigerator 4 is further lowered to -35°C. When the liquid temperature in the crystallizer 3 is -35°C, observe whether small crystal grains are generated in the liquid on a notebook connected to the online crystallization detector 6, and keep recording for 20 minutes;
[0114] Step 12: In step 11, it is observed that small crystals are generated and grow in the electrolyte, and the sample No. 2 has reached the crystallization condition at -35°C. The temperature of the refrigerator 4 is set to -32.5°C. When the liquid temperature in the crystallizer 3 is -32.5°C, observe whether small crystals are generated in the liquid on a notebook connected to the online crystallization detector 6, and keep recording for 20 minutes;
[0115] Step 13: In step 12, no small grains were observed to be generated and grow in the electrolyte, and it is believed that the crystallization temperature of the sample is -33.75°C.
[0116] The above methods are within the scope of protection for the modification of the crystallization characteristics test device and the improvement of the method for the solution involved in other redox flow batteries except iron-chromium flow batteries.
[0117] Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or make equivalent replacements for some of the technical features therein; and these modifications or replacements do not make the essence of the corresponding technical solutions deviate from the spirit and scope of the technical solutions of the embodiments of the present invention.
Claims
1. A test device for studying the crystallization characteristics of an iron-chromium flow battery electrolyte, characterized in that: include: A crystallizer (3), a refrigerator (4), a stirrer (5) and an online crystallization detector (6); The online crystallization detector (6) is connected to a detector probe (2); The detector probe (2) extends 2 to 3 cm below the liquid surface of the crystallizer (3); The stirrer (5) is connected to the crystallizer (3); The refrigerator (4) is connected to the crystallizer (3) via a pipeline.
2. The testing device for studying the crystallization characteristics of the electrolyte of the iron-chromium flow battery according to claim 1, characterized in that: The stirrer (5) comprises a motor, a stirring shaft and stirring blades; The motor is connected to one end of the stirring shaft; The other end of the stirring shaft is connected to the stirring blade; The stirring blade extends below the liquid level of the crystallizer (3); The rotation speed of the stirrer (5) is set to 60-480 r / min.
3. The testing device for studying the crystallization characteristics of the electrolyte of the iron-chromium flow battery according to claim 1, characterized in that: Also includes: Bracket (1); The support (1) is fixedly connected to the online crystallization detector (6) and is used to fix the online crystallization detector (6).
4. The testing device for studying the crystallization characteristics of the electrolyte of the iron-chromium flow battery according to claim 1, characterized in that: Also includes: High purity air bottle (7); The high-purity air bottle (7) is connected to the online crystallization detector (6) via a pipeline.
5. The testing device for studying the crystallization characteristics of the electrolyte of the iron-chromium flow battery according to claim 4, characterized in that: Also includes: A first pressure reducing valve (9); The outlet of the high-purity air bottle (7) is provided with a first pressure reducing valve (9); One end of the first pressure reducing valve (9) is connected to the online crystallization detector (6) through a pipeline; The first pressure reducing valve (9) is set to 0.2-0.4 MPa.
6. The testing device for studying the crystallization characteristics of the electrolyte of the iron-chromium flow battery according to claim 1, characterized in that: Also includes: High purity nitrogen cylinder (8); The high-purity nitrogen bottle (8) is connected to the crystallizer (3) via a pipeline.
7. The testing device for studying the crystallization characteristics of the electrolyte of the iron-chromium flow battery according to claim 6, characterized in that: Also includes: A second pressure reducing valve (10); The outlet of the high-purity nitrogen bottle (8) is provided with a second pressure reducing valve (10); One end of the second pressure reducing valve (10) is connected to the crystallizer (3) through a pipeline; The second pressure reducing valve (10) is set to 0.3-0.5 MPa.
8. The testing device for studying the crystallization characteristics of the electrolyte of the iron-chromium flow battery according to claim 1, characterized in that: Also includes: Control unit; The control unit is electrically connected to the refrigerator (4), the stirrer (5) and the online crystallization detector (6) respectively.
9. The testing device for studying the crystallization characteristics of the electrolyte of the iron-chromium flow battery according to claim 1, characterized in that: The crystallizer (3) is provided with four interfaces.